Industrial del café how the incorporation of taxable new concepts, sources of income which are to increase be held tax revenues in the municipality of Montería (Cordoba) (2014)
Taxes have been established in the legislation of all countries of the world as a source of state funding. These forms of tax character arising from the need to invest in the territories and in turn cover having public administration in each state. Worth mentioning that taxes are set taking into account the principles of legality, legal certainty, generality, escalation, economic, efficiency, among others, which must abide by constitutional requirements, and take into account the tax capacity of each taxpayers, in terms of establishing a ratio between economic activity that they perform and the type of property owned. In turn, the taxes in Colombia are set by state agencies in the levels at which the public administration of the country is divided: national, departmental, municipal and district. Under the rules governing this matter, these institutions apply mechanisms for the collection of taxes due to them by legal mandate. In Monteria commercial activity and property have had a growth spurt according to its population, which has contributed to the emergence of new companies that allow the development of this city and the consolidation of a large number of taxpayers who have helped to progress region. Worth pointing out that the most important taxes for this city are of Industry and Commerce, Unified Property, vehicles, etc., which constitute one of the sources of revenue for the municipality. Regarding the tax ICA is relevant that the same gravel commercial, industrial and service activity, for this reason it requires employers to know which concepts subject to state and you should cancel the municipal treasury are. Regarding the property tax, it is clear that it is an annual tax levied on the City character, urban and rural real estate and property tax fuses, parks and tree planting, and socioeconomic stratification surcharge cadastral survey, which collects municipality of Monteria on property valuation fixed by Codazzi, thereby determining the taxable base of the tax. Furthermore, the vehicle tax is as operative event ownership or possession of the rolling and your tax basis is determined according to the table set each year by order issued by the Transport Ministry. Having stated the above, it is imperative that local authorities the case prompt the Municipality of Monteria, create and enter into the status of income, a suitable and effective every day to protect the municipal collection and in turn serve as mechanisms for generating an increase in the tax culture of taxpayers or taxpayers. This, since ignorance of tax laws is no excuse for violating the tax obligations of the municipality.